The genus Xylaria (Xylariaceae) in the south of China—6. A new Xylaria species based on morphological and molecular characters - Ma, Hai-Xia; Vasilyeva, Larissa; Li, Yu (Phytotaxa, 2013)
Xylaria fusispora, an undescribed species of Xylaria (Xylariales, Xylariaceae), is described and illustrated as a new species based on collections from Guizhou Province, China. Both morphology and phylogenetic analysis of nrDNA ITS sequences support the establishment of this new species. The fungus is characterized by its fusoid-equilateral ascospores and an ascus apical ring not bluing in Melzer’s reagent. The differences between the new species and the related fungi are discussed.